Indikacije in učinkovitost zdravljenja spastičnosti z intratekalno črpalko - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2023)
In some patients severe spasticity of cerebral or spinal origin cannot be treated succesfully with conventional oral medication or physical modalities. Intrathecal baclofen therapy with implanted pump has been an effective treatment since mid-80s. Baclofen (Lioresal) is a muscle relaxant and potent GABA agonist that acts via GABAb receptors at the posterior columns of spinal cord level, to inhibit the release of excitatory neurotransmitters by inhibiting the influx of calcium ions into presynaptic terminals. Such direct binding on spinal cord receptors leads to higher efficiency compared to peroral therapy, in which baclofen does not pass the brain-blood barrier. In Slovenia, there are currently 86 patients with an intrathecal pump implanted; five of those are receiving morphium sulfate as intractable pain therapy. We describe indications and contraindications for intrathecal baclofen therapy, selection and preparation of patients for surgery, the surgical procedure of pump implantation, long term follow-up with pump refill procedure, and possible complications of intrathecal baclofen therapy. In addition, the experiences of the Centre for Spasticity Treatment at the University Rehabilitation Institute Republic of Slovenia in Ljubljana are presented.
Keywords: baclofen pump; baklofenska črpalka; intratekalni baklofen; intrathecal baclofen; Muscle Spasticity; okvara zgornjega motoričnega nevrona; rehabilitacija; rehabilitation; spasticity; spastičnost; upper motor neuron lesion